Influence of different separating mediums applied on the immediate dentin sealing in the tensile strength of temporary restorations - Simões, Ingrid Ísis Nogueira; Reis, Kátia Rodrigues (Brazilian Dental Science, 2022)
Objective: To evaluate the ability of different separating mediums to prevent adhesion between provisionalrestorations and hybridized dentin surfaces when used with the Immediate Dentin Sealing technique (IDS).Material and Methods: 120 extracted human teeth — 40 premolars and 80 molars — were selected to integrateacrylics samples separated into 4 different groups (n=10) according to the separating medium used for IDSprotection. Forty samples were made of three teeth mounted in a self-cure acrylic resin block (Jet, Classic, SãoPaulo, Brazil) arranged side by side, simulating the positioning and proximal contacts present in the dental archbetween the second premolar, first molar and second molar. A standard dental preparation for ultra-thin occlusalveneer was performed and complete occlusal dentin exposure was achieved by selective removal of the occlusalenamel with a high-speed conical round burr (Code: 1801.4138 FG, KG Sorensen, Medical Burs Ind. e Com. dePontas e Brocas Cirúrgicas Ltda, São Paulo, Brazil). Dentin hybridization were performed on the control groupand 3 different groups of separating mediums (n=10): PC—commercial provisional separating agent (Pro-VCoat, Bisco, Schaumburg, USA); GG—glycerin gel (K-Y Gel; Johnson & Johnson Industry and Commerce LTDA,São Paulo, Brazil); PJ—petroleum jelly (Rioquímica, São Paulo, Brazil). Provisionalization were manufacturedon the prepared teeth. After 2 weeks, the tensile test was performed, and the analysis of the failure pattern wasperformed by 3D laser confocal microscopy and Scanning Electron Microscopy (SEM). The data were analyzedwith the 1-way ANOVA and the Tukey test (a = 0.05). Results: Significantly lower tensile strength values werefound for the commercial provisional separating agent (30.39 ± 10.01 N) compared to others (p < 0.05).Conclusion: The commercial provisional separating agent showed greater effectiveness on protecting hybridizeddentin against the provisional restorations.KEYWORDSDental bonding agent; Dental restoration temporary; Immediate dentin sealing.